8 things we hate about I.T. : how to move beyond the frustrations to form a new partnership with I.T. - Cramm, Susan (Harvard Business Press, 2010)
Helps us in understanding differences between operational and IT managers - in backgrounds, personality, pressures, and incentives. This title explains how differences prevent operational managers and IT from communicating what, why, and how they do what they do. It presents practical strategies for overcoming the difficulty